2008
DOI: 10.33349/2008.67.2604
|View full text |Cite
|
Sign up to set email alerts
|

Dioses y antepasados que salen de las piedras

Abstract: Las transformaciones económicas y sociales de comienzos del Holoceno tienen en la progresiva implantación de las figuras humanas en los registros gráficos uno de los más nítidos parámetros de cambio entre las grafías de los cazadores del Paleolítico Superior y las de los agricultores neolíticos. Establecer argumentos acerca del significado de estas imágenes cuenta con la posibilidad contextual que ofrecen las construcciones megalíticas. En este artículo se reflexiona, a partir de la tradición y el conocimiento… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 4 publications
0
4
0
1
Order By: Relevance
“…Most megalithic monuments with carved motifs have also been found to have painted motifs when appropriate methodologies are applied. The presence of red, black and white pigments confirms the ritual value of colour in these funerary contexts (Bueno Ramírez & de Balbín Behrmann 1992; Carrera Ramírez & Fábregas Valcarce 2002; Bueno Ramírez et al 2007, 2008: 52; Carrera Ramírez 2011).…”
Section: The Role Of Colour In Megalithic Monumentsmentioning
confidence: 53%
See 1 more Smart Citation
“…Most megalithic monuments with carved motifs have also been found to have painted motifs when appropriate methodologies are applied. The presence of red, black and white pigments confirms the ritual value of colour in these funerary contexts (Bueno Ramírez & de Balbín Behrmann 1992; Carrera Ramírez & Fábregas Valcarce 2002; Bueno Ramírez et al 2007, 2008: 52; Carrera Ramírez 2011).…”
Section: The Role Of Colour In Megalithic Monumentsmentioning
confidence: 53%
“…It has previously been suggested that the construction of chambered tombs in Brittany was preceded by a phase with menhirs (Midgley 2013: 422). There is increasing evidence from the Iberian Peninsula for the erection of large standing stones before the building of the first chambered tombs (Bueno Ramírez et al 2007, 2012). It indicates that the use of standing stones was more extensive than previously thought, and that it was perhaps part of a general process of monumentalisation (Laporte 2010).…”
Section: Brittany the Iberian Peninsula And Atlantic Megalithic Artmentioning
confidence: 99%
“…At Montelirio, some pieces from the cover of the monument are reused stelae. We know this also happened at the Menga dolmen (Bueno Ramírez et al 2008b). The remarkable stone covering the chamber was engraved before being placed in its present position.…”
Section: Ancestors As a Reference Pointmentioning
confidence: 89%
“…The Palacio III tholos clearly shows that, lacking as they do a structural function (they did not support any weight), the role that these slabs played was to provide a smooth, even and 'noble' surface (literally, a "canvass") over which graphic motifs could be painted, hence conveying notions of ancestry and mythology . It should be remembered that these materials were also commonly used to manufacture the socalled 'plaque idols' that, painted or engraved with geometric motifs very similar to those on the slabs in the Palacio III tholos, did also evoke deities or ancestors (Bueno Ramírez and Balbín Behrmann 1992;Bueno Ramírez et al 2008;Lillios 2008;.…”
Section: Discussionmentioning
confidence: 99%